UK Food Standards Agency Workshop Report: the effects of the dietary n-6:n-3 fatty acid ratio on cardiovascular health. - Stanley, J; Elsom, R; Calder, P; Griffin, B; Harris, W; Jebb, SA; Lovegrove, J; Moore, C; Riemersma, R; Sanders, T (2007)
This report summarises a workshop convened by the UK Food Standards Agency (FSA) on 11 September 2006 to review the results of three FSA-funded studies and other recent research on effects of the dietary n-6:n-3 fatty acid ratio on cardiovascular health. The objective of this workshop was to reach a clear conclusion on whether or not it was worth funding any further research in this area. On the basis of this review of the experimental evidence and on theoretical grounds, it was concluded that the n-6:n-3 fatty acid ratio is not a useful concept and that it distracts attention away from increasing absolute intakes of long-chain n-3 fatty acids which have been shown to have beneficial effects on cardiovascular health. Other markers of fatty acid intake, that more closely relate to physiological function, may be more useful.